2016
DOI: 10.1530/edm-15-0136
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with sitagliptin and vitamin D in a patient with latent autoimmune diabetes in adults

Abstract: SummaryLatent autoimmune diabetes in adults (LADA) is a relatively new type of diabetes with a clinical phenotype of type 2 diabetes (T2D) and an immunological milieu characterized by high titers of islet autoantibodies, resembling the immunological profile of type 1 diabetes (T1D). Herein, we report a case of a young male, diagnosed with LADA based on both clinical presentation and positive anti-glutamic acid decarboxylase antibodies (GAD-abs), which were normalized after combined treatment with a dipeptidyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
2
13
0
3
Order By: Relevance
“…Uma das novas propostas de classificação é centrada em células beta, englobando todos os subtipos de DM conhecidos, apoiando melhores práticas em gestão desta patologia através da identificação das vias que promovem a hiperglicemia, dirigindo o tratamento para disfunções específicas e com relação à terapêutica, as sulfonilureias têm mostrado a indução de apoptose em cultura de células beta (2). Em contrapartida, há relatos de uma melhoria significativa da resposta das células beta com o tratamento à base de inibidores de DPP4, entre outras drogas mais modernas (4). Essas evidências denotam que a situação relativa ao tratamento medicamentoso também precisa ser revista.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Uma das novas propostas de classificação é centrada em células beta, englobando todos os subtipos de DM conhecidos, apoiando melhores práticas em gestão desta patologia através da identificação das vias que promovem a hiperglicemia, dirigindo o tratamento para disfunções específicas e com relação à terapêutica, as sulfonilureias têm mostrado a indução de apoptose em cultura de células beta (2). Em contrapartida, há relatos de uma melhoria significativa da resposta das células beta com o tratamento à base de inibidores de DPP4, entre outras drogas mais modernas (4). Essas evidências denotam que a situação relativa ao tratamento medicamentoso também precisa ser revista.…”
Section: Discussionunclassified
“…Quando o quadro da paciente e a sua evolução foram considerados, a paciente foi diagnosticada com DD. A literatura relata o caso de um paciente diagnosticado com LADA, apesar dos 31 anos, apresentando um quadro extremamente semelhante ao desta paciente: hiperglicemia (300mg/dl), poliúria, polidipsia, perda de peso e "visão embaçada" e que devido à recusa veemente de ser tratado com insulina, foi tratado com uma terapia alternativa com inibidor da dipeptil peptidase (Sitagliptina®) e vitamina D, pois havia hipovitaminose, obtendo-se excelente controle glicêmico dentro de oito semanas, o que persistiu por dois anos de acompanhamento (4). Relatos como este motivam a terapêutica centrada no reconhecimento das vias produtoras de hiperglicemia em cada paciente e reforçam a necessidade de uma classificação mais útil para a Diabetes, na prática médica.…”
Section: Conclusãounclassified
See 1 more Smart Citation
“…Rapti et al . (25) presented a case of a 31-year-old man with LADA treated with a combination of metformin 850 mg and sitagliptin 50 mg twice daily along with vitamin D supplementation (2000 IU/day). After treatment, the patient’s serum HbA1c level decreased from 9.6% to 5.2% and his positive anti-GAD level (which was 32 IU/mL at baseline) became negative.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports [92][93][94][95] on autoimmune diabetes patients have found that DPP-4 inhibitor treatment, alone or in combination with other drugs, significantly improved glucose control and reduced insulin requirements, with a good tolerance profile. Therefore, DPP-4 inhibitors may also benefit autoimmune diabetes.…”
Section: Clinical Effects Of Dpp-4 Inhibitor On Autoimmune Diabetesmentioning
confidence: 99%